Total Quality Management Implementation: Investigating the Impact on the Performance of Pakistani Universities - Khan, Rizwan; Malik, Sidra; Rehman, Muhammad Zia Ur (Annals of Human and Social Sciences, 2023)
This study investigated the impact of the quality management implementation on the performance of the universities of Pakistan. For this purpose, the researcher(s) sampled the university teachers teaching in the department of Education in the private universities. There were 300 teachers from social sciences discipline who have been selected with the help of Cluster sampling from 12 Public and Private Universities across Punjab, Pakistan. The data related to Total Quality Management have been collected with the help of a close-ended questionnaire comprising 35 items. Whereas the data related to the university performance has been measured with scale comprising 33 items. This scale has been adapted from Afzal (2022). The results revealed a significantly moderate effect of TQM was on the performance of the universities. It has been recommended based on the results that the TQM should be implemented by the universities with true letter and spirit so that the universities’ performance may be enhanced.